Pembiayaan Murabahah Pada Perbankan Syariah dalam Perspektif Hukum di Indonesia - Hakim, Lukmanul; Anwar, Amelia (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
Islamic Bank is a bank that uses Sharia principles in conducting its business activities where the legal basis of the implementation of sharia principles refers to AlQuran and Al-Hadith as well as some other regulations related to the business activities of Islamic banks namely Financial Intermediary which collects and distributes funds to the public. in distribution activities to this community there are some financing that is run in the principles of sharia such as financing the sale or we used to know the agreement murbahah. Murabahah is one of the most common types of contracts (akad) applied in financing activities of sharia banking. Murabahah is applied through the mechanism of sale and purchase of goods with the addition of margin as profit to be obtained by the bank.